2021
DOI: 10.1159/000513325
|View full text |Cite
|
Sign up to set email alerts
|

Role of Upper Respiratory Microbiota and Virome in Childhood Rhinitis and Wheeze: Collegium Internationale Allergologicum Update 2021

Abstract: There is emerging evidence that the respiratory microbiota influences airway health, and there has been intense research interest in its role in respiratory infections and allergic airway disorders. This review aims to summarize current knowledge of nasal microbiome and virome and their associations with childhood rhinitis and wheeze. The healthy infant nasal microbiome is dominated by <i>Corynebacteriaceae</i> and <i>Staphylococcaceae</i>. In contrast, infants who subsequently develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…While some of these nonhuman viruses were sparsely detected, reads for bacteriophages were consistently detected at varying amount in all participants. This support previous reports on HA of bacteriophages in the respiratory tract with the potential to prime and modulate host immune responses in children 39,40 . Additionally, mNGS further enabled the simultaneous detection of bacteria co‐infection in 24 (28.5%) patients despite enrichment for RNA viruses.…”
Section: Discussionsupporting
confidence: 87%
“…While some of these nonhuman viruses were sparsely detected, reads for bacteriophages were consistently detected at varying amount in all participants. This support previous reports on HA of bacteriophages in the respiratory tract with the potential to prime and modulate host immune responses in children 39,40 . Additionally, mNGS further enabled the simultaneous detection of bacteria co‐infection in 24 (28.5%) patients despite enrichment for RNA viruses.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, boys had an increased risk of experiencing allergic disease relative to girls as reported by the majority of studies [28][29][30][31] , consistent with the ndings of the present study, as sex was listed among the top features when predicting the risk for asthma, rhinitis and eczema in children. The reasons for this sex-speci c contribution are not fully understood; however, it might be interpreted by the varying responses to environmental or occupational exposures involving immunological and hormonal factors between boys and girls [32][33][34][35] . The same cases were found for upper respiratory infection and age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it breaks the traditional opinion that the upper respiratory tract is the only source of microorganisms in the lower respiratory tract. Besides, we found that respiratory tract microbes may be various in different populations, such as newborns ( 11 ). Biological colonization also has specific differences because of other delivery methods ( 12 ).…”
Section: Pulmonary Microbiotamentioning
confidence: 94%